Gastric intestinal metaplasia as detected by a monoclonal antibody is highly associated with gastric adenocarcinoma. Issue 6 (1st June 2003) - Mirza, Z K; Das, K K; Slate, J; Mapitigama, R N; Amenta, P S; Griffel, L H; Ramsundar, L; Watari, J; Yokota, K; Tanabe, H; Sato, T; Kohgo, Y; et al.
Abstract : Background: Some forms of gastric intestinal metaplasia (GIM) may be precancerous but the cellular phenotype that predisposes to gastric carcinogenesis is not well characterised. Mucin staining, as a means of differentiating GIM, is difficult. A monoclonal antibody, mAb Das-1 (initially called 7E12 H12 ), whose staining is phenotypically specific to colon epithelium, was used to investigate this issue. Methods: Using mAb Das-1, by a sensitive immunoperoxidase assay, we examined histologically confirmed GIM specimens from two countries, the USA and Japan. A total of 150 patients comprised three groups: group A, GIM (fields away from the cancer area) from patients with gastric carcinoma (n=60); group B, GIM with chronic gastritis (without gastric carcinoma) (n=72); and group C, chronic gastritis without GIM (n=18). Results: Fifty six of 60 (93%) patients with GIM (both goblet and non-goblet metaplastic cells) from group A reacted intensely with mAb Das-1. Cancer areas from the same 56 patients also reacted. In contrast, 25/72 (35%) samples of GIM from patients in group B reacted with mAb Das-1 (group A v B, p<0.0001). None of the samples from group C reacted with the mAb. Conclusions: Reactivity of mAb Das-1 is clinically useful to simplify and differentiate the phenotypes of GIM. The colonic phenotype of GIM, as identified by mAb Das-1, is strongly associated with gastric carcinoma.